Mediating role of wellbeing among organizational virtuousness, emotional intelligence and job performance in post-pandemic COVID-19 - Arshad, Muhammad Ali; Arshad, Darwina; Zakaria, Nazlina (Frontiers in Psychology, 2023)
It is devastating to people’s mental and emotional health to be exposed to the COVID-19 pandemic and the multifaceted response strategies are required to curb it. As a result of social distancing and self-isolation, people have faced many challenges in their lives. The suffering is even greater at the workplace where the employees are working with the fear of getting exposed to the virus and its new variants which is adversely affecting their wellbeing. This study explores and tests a model that extends the wellbeing research across organizational settings and targets the crucial factors that lead to job performance improvement even in the post pandemic COVID-19 situation. To improve both in-role performance and extra-role performance behaviors in the Pakistan banking sector, organizational virtue (also known as organizational virtuousness) and internal virtue (also known as emotional intelligence) are examined. Data were collected from the 416 bank employees using disproportionate stratified sampling technique. In the bank sector of Pakistan, wellbeing was identified as the key psychological factor that relates the in-role performance and extra-role performance to internal and organizational factors. Research findings also determined that conceptualizing subjective wellbeing in the context of work is more meaningful in understanding its relationship with the workplace variables than the general or global subjective wellbeing.